DIGITAL STORYTELLING TO IMPROVE STUDENTS’ MASTERY IN WRITING NARRATIVE (ELT Forum: Journal of English Language Teaching, 2013)
This study is an experimental study. It aims to find out whether teaching narrative text using digital storytelling is effective to enhance students’ mastery in writing. This research also reveal the significant difference in the achievement between students who are taught using digital storytelling and those who are taught using conventional technique. In order to achieve those objectives, I conducted an experimental study. The population of this study was the eighth graders of SMPN 1 Grobogan. The experimental group was VIII-1 and the control group was VIII-2. The experimental group was taught using digital storytelling and the control group was taught using conventional technique. The result after a treatment was given shows that the mean of experimental group was higher than the control group. Therefore, there is a significant difference in students’ achievement that was taught using digital storytelling and using conventional technique. It is concluded the use of digital storytelling as visual aid can improve students’ mastery in writing narrative.